Procesos decisorios y eficiencia productiva: Ganadería argentina - Marcos Gallacher; Daniel Lema (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2018)
– During the last decades substantial increases in both output as well as productivity have taken place in Argentine cereal and oilseed production. This has not been the case of livestock production, where both output as well as productivity increases have been modest. This paper - of an exploratory nature - analyzes some of the challenges involved in estimating productivity differences in livestock enterprises. The objective is to point out data needs to (i) quantify productivity differences and (ii) explain why these differences exist. This paper is a part of a research project focused on the measurement of efficiency of livestock production using farm-level data.
Keywords: 330